Comparative Effects of Balanites aegyptiaca and Spirulina Supplementation on Serum Calcium, Phosphorus, and Hormonal Profiles in Male Rabbits - Fayrouz Khaled; Antsar Husayn (AlQalam Journal of Medical and Applied Sciences, 2025)
This study evaluated the influence of Balanites aegyptiaca and Spirulina supplementation on mineral balance and key reproductive hormones in male rabbits. Spirulina produced a clear elevation in serum calcium, indicating enhanced mineral absorption and regulation, whereas Balanites aegyptiaca showed only a mild effect. In contrast, phosphorus levels remained stable across all groups, reflecting intact physiological control of phosphorus homeostasis. Hormonal analysis revealed that both supplements reduced estrogen and cortisol concentrations, suggesting a potential stress-modulating effect. Meanwhile, FSH, testosterone, and LH showed a gradual improvement, with Spirulina demonstrating the most pronounced enhancement in reproductive hormone profiles. Overall, the findings indicate that Spirulina has a stronger impact on calcium metabolism and reproductive endocrine function, while Balanites aegyptiaca provides moderate hormonal benefits without altering phosphorus stability. These outcomes support the possible use of both supplements, especially Spirulina, in improving mineral status and reproductive health in male rabbits.